External impact assessment of IFPRI's 2020 Vision for Food, Agriculture and the Environment Initiative - Paarlberg, Robert L. (International Food Policy Research Institute, 1999)
The 2020 Vision initiative of the International Food Policy Research Institute (IFPRI) was launched late in 1993, at a time of growing global complacency regarding international food security questions. The first phase of the 2020 Vision initiative (1993–96) featured the development of an innovative forward-looking partial equilibrium model of the international food and agriculture sector; the hosting of an extensive series of high profile conferences, workshops, and regional meetings; the publication and distribution of numerous substantive discussion papers, policy briefs, and regional synthesis papers; and the regular publication of a topical newsletter. The goal was to refocus attention on current and future challenges in areas such as food security, agricultural development, rural poverty, and environmental protection; to catalyze a new consensus on these issues within the international policy community; and to encourage policy leaders—both in the donor community and in the developing world—to commit more energy and resources to resolve food security concerns. The present report is an independent effort, commissioned by IFPRI, to measure the actual impact, to date, of this ongoing 2020 Vision initiative. The impacts examined include impacts on three different audiences: researchers and educators, international policy leaders, and developing-country policy leaders. For each of these audiences, an assessment is given as to whether the 2020 Vision initiative significantly “reached” the audience in question with its materials and messages; whether 2020 had an impact on the policy thinking of this audience; and whether 2020 actually catalyzed any new policy actions by this audience. 2020 activities, from materials published by other organizations working in the food security and agricultural development area, and from materials gathered from donors, international organizations, and the nongovernmental organization (NGO) community.